2018
DOI: 10.24193/adn.11.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Attitudes Towards Probability and Statistics and Academic Achievement on Higher Education

Abstract: A simple analysis of the learners' academic status at different levels of education shows that these learners have poor performance in probability and statistics subject and they have negative attitude to this subject. Therefore, the aim of this study is to investigate the relationship between the attitude and academic achievement of 134 students of three classes of a compulsory subject of the fourth period aimed at probabilistic and statistical content, at a federal university, in the state of São Paulo, Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…Studies have shown that statistics is one of the mathematics areas teachers and students have difficulties. Oliveira Junior, Zamora, Azevedo de Oliveira and Costa de Souza (2018) observed that analysing the learners' academic status at different levels of education shows that these learners have poor performance in Probability and Statistics, and they have negative attitude towards the subject. In the study where they investigated the relationship between attitude and academic achievement of 134 students in probability and statistics at a Federal University in the state of Sao Paulo, Brazi : on utility, anxiety, trust, pleasure and motivation scales, results indicated students lack confidence in solving Statistical and Probabilistic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that statistics is one of the mathematics areas teachers and students have difficulties. Oliveira Junior, Zamora, Azevedo de Oliveira and Costa de Souza (2018) observed that analysing the learners' academic status at different levels of education shows that these learners have poor performance in Probability and Statistics, and they have negative attitude towards the subject. In the study where they investigated the relationship between attitude and academic achievement of 134 students in probability and statistics at a Federal University in the state of Sao Paulo, Brazi : on utility, anxiety, trust, pleasure and motivation scales, results indicated students lack confidence in solving Statistical and Probabilistic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de los principales resultados de estas investigaciones destaca el hecho de que el nivel de actitud del estudiantado decrece con el tiempo en cuanto a la presencia de comportamientos diferenciales de los ítems en variables como edad y disciplina académica, la confirmación de marcos conceptuales, la correlación de las actitudes con otros constructos, como la autoeficacia o la ansiedad, y, ante todo, el papel relevante que juegan las actitudes en el aprendizaje de la Estadística (de Oliveira et al, 2018;Nielsen y Kreiner, 2018;Rodríguez y Gil, 2019;van Appel y Durandt, 2018).…”
Section: Actitudes Hacia La Estadísticaunclassified
“…It is, however, one thing to need to take courses in statistics and another thing to have the right attitude towards it. Students' attitude towards statistics is one of the major concerns in statistics education given the large number of articles in this regard (e.g., Ashaari et al, 2011;Cashin & Elmore, 2005;Gal et al, 1997;Garfield et al, 2002;Gundlach et al, 2015;Oliveira Júnior et al, 2018;Schau & Emmioglu, 2012;Schau et al, 1995;Whitaker et al, 2022), and the fact that different scales have been developed for this purpose. The most popular attitude scale has hitherto been the Survey of Attitudes Toward Statistics (SATS) scale by Schau et al (1995), with a later version in 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular attitude scale has hitherto been the Survey of Attitudes Toward Statistics (SATS) scale by Schau et al (1995), with a later version in 2003. Some details about various scales can be found in Oliveira Júnior et al (2018), where a study on student's attitudes towards probability and statistics was presented. One of the conclusions made by these authors was that the study of attitudes contributes to the effectiveness of the educational process in the teaching of probability and statistics.…”
Section: Introductionmentioning
confidence: 99%